The association between hypoxia, chronic ischemia and alters prostate structure and progress of chronic prostatic disease - Luisetto, Mauro; Ahmadabadi, Behzad Nili; Mashori, Ghulam Rasool; Hamid, Gamal Abdul (Archives of Pharmacy and Pharmaceutical Sciences, 2019)
Chronic prostatitis today show high level of relapses and recurrent pathological events even if using the best pharmacological therapy. A better understanding of physiopathological effect of ischemic hypoxic condition (pelvic, prostate tissue) and the lymphatic congestion in same body region contribute in evolution of a complex condition. The same focusing the strategy in biofilm reduction or in leukocyte infiltration can be a right way to reduce relapses and progression of the prostatic disease. Hypoxia is also related to prostatic cancer progression and prostatic biofilm if responsible of making a new micro- environment often drug resistance. A deep knowledge in this kind of phenomena can improve the clinical effect of drug therapy.